Reviewing the efficiency of photobiomodulation therapy in oncological treatment - Luitel, Bibhus; Duggisani, Tanush; Luitel, Anuj; LaRocco, John (Frontiers in Oncology, 2024)
The aim of the present systematic review is to evaluate the effects of different photobiomodulation therapy (PBMT) approaches in oncological treatment practices. The review follows the PRISMA guidelines. Specifically, the review is composed of laser PBMT and LED PBMT. A total of 23 studies were included, 14 investigating laser PBMT and 9 examining LED PBMT. In vitro studies demonstrated laser PBMT’s potential to induce apoptosis and cytotoxicity in various cancer cell lines while enhancing sensitivity to chemotherapeutics and natural compounds. However, some studies highlighted divergent effects between in vitro (promoted proliferation) and in vivo xenograft models (slowed tumor growth) for certain laser wavelengths. LED PBMT studies showed blue light inhibited melanoma and pancreatic cancer cell growth, potentially via ROS generation, while red light raised concerns about enhancing oral cancer invasiveness. Both modalities mitigated treatment side effects like oral mucositis, xerostomia, peripheral neuropathy, and improved quality of life. While promising, the outcomes varied based on light parameters, cancer type, and experimental setting, necessitating further optimization of PBMT protocols through well-designed studies to establish long-term safety and efficacy across clinical scenarios.